(untitled) (Journal of Preventive and Social Medicine, 2021)
Background: Aging is universal and it is inescapable. Health problems of elderly people are a global emerging issue. Body mass index (BMI) is a test often used to help medical professiona ls to assess nutritional status along with overall fitness and risk for disease in elderly. This study was conducted to assess the BMI and common geriatric health problems among elderly retired armed forces personnel. Methods: This cross-sectional study was conducted among purposively selected 226 elderly retired armed forces personnel in both outpatient and inpatient departments of the Combined Military Hospital (CMH), Dhaka Cantonment from July 2018 to Jun e 2019. The study aimed to assess the association between BMI and common geriatric health problems. A questionnaire comprising of all the variables of interest were developed and used for data collection by face to face interview. Data were also collected by physical measurement and reviewing medical documents of the participants. Results: Among the participants, majority (32.3%) had BMI c:25, 31 .9 % had 23-24.9, 30. 1 % had 18.5-22.9 and 5.8% had <18 .5 BMl group. Average number of morbidities perparticipant was 2.59. Out of all , 20.5% had hypertension, 13. 7% had heart disease , 13.1 % had diabetes, 1 2.5% had respiratory disease, 8.4% had dental disease, 7.5% had cataract, 7.5% had prostate enlargement, 5.8% had cancer, 5.6% hadarthritis and 5.5% hadear disease. Association of BMI of participants with hypertensi on, heart disease was found statistically significant (p<0.05). No significant association was found with diabetes and respiratory disease ( p<0.05). Conclusion: Nutritional status of the elderly should be emphasized for prevention and control of health problems in retired armed forces elderly; for that BMl could be crucial indicator. JOPSOM 2020; 39(1): 14-20